2012
DOI: 10.1016/j.difgeo.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Nullity conditions in paracontact geometry

Abstract: The paper is a complete study of paracontact metric manifolds for which the Reeb vector field of the underlying contact structure satisfies a nullity condition (the condition (1.2), for some real numbers and k and μ. This class of pseudo-Riemannian manifolds, which includes para-Sasakian manifolds, was recently defined in Cappelletti Montano (2010) [13]. In this paper we show in fact that there is a kind of duality between those manifolds and contact metric (k,μ)-spaces. In particular, we prove that, under so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 26 publications
1
67
0
Order By: Relevance
“…The importance of paracontact geometry, and in particular of para-Sasakian geometry, has been pointed out especially in the last years by several papers highlighting the interplays with the theory of para-Kähler manifolds and its role in semi-Riemannian geometry and mathematical physics (cf. e.g., [5] , [13]).…”
Section: Preliminariesmentioning
confidence: 99%
“…The importance of paracontact geometry, and in particular of para-Sasakian geometry, has been pointed out especially in the last years by several papers highlighting the interplays with the theory of para-Kähler manifolds and its role in semi-Riemannian geometry and mathematical physics (cf. e.g., [5] , [13]).…”
Section: Preliminariesmentioning
confidence: 99%
“…This new class of pseudo-Riemannian manifolds was introduced in [6]. In [7], the authors showed that while the values ofκ andμ change the form of (1.1) remains unchanged under D-homothetic deformations. There are differences between a contact metric (κ, µ)-space (M 2n+1 , ϕ, ξ, η, g) and a paracontact metric (κ,μ)-space (M 2n+1 ,φ, ξ, η,g).…”
Section: Introductionmentioning
confidence: 99%
“…In [6], the authors construct an example of a 5-dimensional (k, µ)-paracontact metric manifold. With the help of that example we construct a new example as follows:…”
Section: Example Of a 5-dimensional (K µ)-Paracontact Metric Manifoldmentioning
confidence: 99%
“…Let g be the Lie algebra of a Lie group G admits a basis {e 1 , e 2 , e 3 , e 4 , e 5 } such that [6] [e 1 We consider the metric such that g(e 1 , e 1 ) = g(e 4 , e 4 ) = g(e 5 , e 5 ) = 1, g(e 2 , e 2 ) = g(e 3 , e 3 ) = −1 and g(e i , e j ) = 0, for i = j.…”
Section: Example Of a 5-dimensional (K µ)-Paracontact Metric Manifoldmentioning
confidence: 99%
See 1 more Smart Citation